Research on the impact of performance evaluation cycle on the relationship between performance pay intensity and employee exploratory innovation behavior: a conceptual paper - Xue, Jiang; Binti Mat Jusoh, Nurul Hidayu; Alan, Ribka; Robin, Tunung (Human Resources Management Academic Research Society (HRMARS), 2024)
This paper proposes a conceptual model and states valid propositions to be tested by future researchers empirically. The model explicates the effects of performance pay intensity and performance evaluation cycle on employees' exploratory innovation behavior. Being a conceptual paper, it reviewed scholarly articles on the variables of the study in accordance with theoretical perspectives. In this paper, temporal motivation theory and cognitive evaluation theory are used to explain and support this conceptual model. This study will help companies to develop moderate performance pay intensity and performance evaluation cycles to maximize employees' exploratory innovative behaviors, which will help to improve the level of innovation across the enterprise.